Effect of melatonin addition in ovulation induction protocols with clomiphene citrate in management of infertility - Chaudhary, Anjali; Agarwal, Aditi; Tanwar, Meenakshi; Singh, Parul; Negi, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: About 10-12% of couples are unable to conceive by natural means despite concerted efforts and these figures have risen in past few decades. In recent years, effect of oxidative stress on the fertility has been widely recognised. Oxidative stress has been known to affect both male and female fertility reducing sperm count and motility in men, and affecting ovum reserve and quality in women. Melatonin is the secretion of the pineal gland responsible for circadian sleep rhythm has also shown to be good antioxidant. Aim and objective of current study was to study effect of melatonin addition to clomiphene citrate for induction of ovulation with a view to improve conception rates. Methods: This was a retrospective analysis of 52 women with infertility who were given clomiphene citrate with melatonin. Ovulation, conception rates and pregnancy outcomes were noted. Results: We observed 77.8%ovulation rates, and a significantly better conception and live birth rates. Conclusions: Melatonin, as an anti-oxidant may improve, conception and live birth rates when added to clomiphene citrate induction protocols.